The Treaty Port Economy in Modern China : Empirical Studies of Institutional Change and Economic Performance - Myers, Ramon Hawley, 1929-; So, Billy K. L. (Billy Kee Long), 1952- (Book collections on Project MUSE., 2011)
"Through eight empirical studies, this volume explores the interplay between institutional change and economic performance in a constructed model of the treaty port economy in late-Qing and Republican China"--Provided by publisher.